Comparison of the Efficacy of Three Different Bone Regeneration Materials: An Animal Study - Anbu, R. Tamil; Suresh, V.; Gounder, Revathy; Kannan, Abinaya (European Journal of Dentistry, 2019)
Objective The proposed study aimed to evaluate and compare the bone regeneration between commercially available hydroxyapatite–β-tricalcium phosphate (Ossifi; Equinox, the Netherlands), powdered polylactic acid (powdered PLA; Sigma-Aldrich, United States), and three-dimensionally printed PLA (3D-printed PLA; Cubex, SC, United States) using 3D printer (Cube X trio) in an animal model.Materials and Methods Eighteen New Zealand rabbits were divided into three groups with six animals each. Platelet-rich fibrin (PRF) was collected from the venous blood and preserved. Bone defect (4 mm × 2 mm) without disturbing the bone marrow was created and filled with bone graft material (group 1–Ossifi, group 2–powdered PLA, and group 3–3D-printed PLA), over which PRF membranes were placed. The graft material and the barrier were stabilized using resorbable sutures, and all the animals were maintained for 4, 8, and 12 weeks, after which they were euthanized, and bone samples were retrieved. Retrieved bone samples were subjected to radiological and histological analysis.Results The radiographic and histological changes of 3D-printed PLA in comparison with other two materials (Ossifi and powdered PLA) seemed to have a significant difference.Conclusion 3D-printed PLA scaffolds showed positive signs of bone regeneration around the material in continuity defects. PLA material can be a promising alternative bone regenerative material.
Keywords: biomaterials; bone grafts; bone regeneration; bone substitutes; polylactic acid; three-dimensional printed polylactic acid